Optimal solution of PM synchronous motor obtained by gravitational search algorithm - Cvetkovski, Goga; Petkovska, Lidija (IOS Press, 2022)
This paper presents a novel approach to the efficiency improvement of permanent magnet synchronous motor using gravitational search algorithm as an optimization tool. The gravitational search algorithm (GSA) is a recently developed meta-heuristic optimization algorithm, which so far has proven to be quite suitable for solving power engineering optimization problems. The aim of this research work is to implement this novel optimization algorithm for the efficiency improvement of permanent magnet synchronous motor, where the objective function in the optimization process is the efficiency of the investigated motor. Comparative analysis of the initial and a number of optimized solutions of the motor model is performed.
Keywords: Permanent magnet synchronous motor; efficiency; optimization; optimal design; gravitational search algorithm